ANALISIS POLA MINUM DENGAN BERAT BADAN PADA PASIEN GAGAL GINJAL KRONIS DI RUMAH SAKIT UMUM TANGERANG SELATAN - Andriati, Riris; Mutiara, Ayu Indah; Pratiwi, Rita Dwi (NURSING ANALYSIS: Journal of Nursing Research, 2024)
ABSTRACTNon-Communicable Diseases (NCDs) are chronic diseases that cannot be transmitted from individual to other individual. According to (Ministry of Health, 2018) states that kidney failure is included in the list of non-communicable diseases that the government is focusing on controlling. Kidney failure is a disorder in which kidney function decreases in maintaining metabolic fluid and electrolyte balance, resulting in uremia. Research Objective: To determine the relationship between drinking patterns and body weight in chronic kidney failure patients at the South Tangerang City Hospital. Method: The type of research currently used by researchers is using quantitative methods, analytical survey research design and cross sectional research design, namely research that studies the relationship between risk factors (independent) and effect factors (dependent), where observing or measuring variables is carried out once and simultaneously over time. which is the same as the chi square statistical test. Research Results: The relationship between drinking patterns and body weight in chronic kidney failure patients at RSU South Tangerang showed that a small number of respondents had good drinking patterns as many as 17 respondents (16.0%) and almost none with normal body weight there were 4 respondents (5.0%), and there were a small number of respondents who were categorized as close to 10 respondents (9.9%), and there were almost no normal body weights as many as 3 respondents (3.1%) in sufficient category, and a small number with abnormal body weight in the sufficient category were found to be 13 (13.0%). Meanwhile, almost half of the respondents with drinking patterns in the underweight category were found to be 49 respondents (52.0%), and those with normal weight in the undercategory category were found to be a small number of 17 respondents (15.8%). And it was also found that for body weight in the less than normal category, more than half of the respondents were found to be 66 respondents (66.0%). Statistical Test Results: The results showed that there was a relationship between drinking patterns and body weight in chronic kidney failure patients at RSU South Tangerang with a p value of 0.000. Suggestion: It is hoped that there will be implementation with the module for chronic kidney failure patients so that weight monitoring can be implemented in chronic kidney failure patients so that the quality of life for chronic kidney failure patients in the hemodialysis room can be longer. ABSTRAKPenyakit Tidak Menular (PTM) merupakan penyakit kronis yang tidak dapat ditularkan dari individu ke individu lainnya. Menurut  (Kemenkes, 2018) menyebutkan bahwa penyakit gagal ginjal termasuk kedalam daftar penyakit tidak menular yang menjadi fokus pemerintah untuk dikendalikan.Gagal ginjal merupakan sebuah gangguan yang dimana fungsi ginjal mengalami penurunan dalam mempertahankan metabolisme keseimbangan cairan dan elektrolit sehingga menjadi uremia. Tujuan Penelitan: Untuk mengetahui Hubungan Antara Pola Minum Dengan Berat Badan Pada Pasien Gagal Ginjal Kronis Di Rsu Kota Tangerang Selatan. Metode: Jenis penelitian yang digunakan peneliti saat ini yaitu menggunakan metode kuantitatif desain penelitian survei analitik dan rancangan penelitian Cross Sectional, yaitu peneliyian yang mempelajari hubungan antara factor resiko (independen) dengan factor efek (dependen ), dimana melakukan observasi atau pengukuran variable sekali dan sekaligus dengan waktu yang sama dengan uji statistic chi square. Hasil Penelitian:.hubungan antara pola minum dengan berat badan pada pasien gagal ginjal kronis di RSU Tangerang Selatan didapatkan sebagian kecil responden terhadap pola minum yang baik sebanyak 17 responden (16,0%) dan hampir tidak ada dengan berat badan normal didapatkan sebanyak 4 responden (5,0%), serta didapatkan sebagian kecil responden yang berkategorikan cukurp 10 responden (9,9%), dan hamper tidak ada berat badan yang normal sebanyak 3 responden ( 3,1%) dalam kategori cukup, serta sebagian kecil dengan berat badan tidak normal dalam kategori cukup didapatkan sebanyak 13 (13,0%). Sedangkan didapatkan responden dengan pola minum dalam kategori kurang didapatkan hamper setengahnya sebanyak 49 responden (52,0%), dan yang mengalami berat badan normal dalam kategori kurang didapatkan sebagian kecil sebanyak 17 responden (15.8%). Serta didapatkan juga untuk berat badan dalam kategori kurang tidak normal, didapatkan lebih dari setengahnya responden sebanyak 66 responden (66.0%). Hasil Uji Statistik: Didapatkan hasil terdapat hubungan antara pola minum dengan berat badan pada pasien gagal ginjal kronis di RSU Tangerang Selatan dengan p value 0,000. Saran: diharapkan adanya implementasi dengan modul pada pasien gagal ginjal kronis sehingga diberlakukannya pemantauan berat badan pada pasien gagal ginjal kronis agar kualitas hidup pada pasien gagal ginjal kronis diruang hemodialisa bisa lebih panjang.